Nature Photonics - Graydon, Oliver; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Research.)
Launched in January 2007, Nature Photonics is a monthly journal dedicated to publishing topquality, peer-reviewed research in all areas of light generation, manipulation and detection. Coverage extends from research into the fundamental properties of light and how it interacts with matter through to the latest designs of optoelectronic devices and emerging applications that exploit photons.
Keywords: Physics; Quantum physics; Physics, general; Applied and Technical Physics; Quantum Physics